UNDERSTANDING STUDENT PROFILE SMP IT AL-FITYAN GOWA SCHOOL CLASS IX AT PROBLEM SOLVING VIEWED FROM THE REASONING ABILITY OF MATHEMATICS - Ikrimah Ikrimah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
This study is an exploratory study with a qualitative approach that aims to uncover the junior high profile student understanding in solving mathematical problems in terms of mathematical reasoning abilities. The subjects were students of class IX SMP IT Al-Fityan School Gowa consisting of three students with one student has a high mathematical reasoning abilities, one student with mathematical reasoning being, and one student with low mathematical reasoning. Instruments in this study is the researchers themselves as the main instrument that is guided by the mathematical problem solving test, interview, mathematical reasoning ability tests. The study began by determining the subject of research using mathematical reasoning test instruments, and the continuation of TPMM and interviews. Checking the validity of the data using a triangulation of time. The data collection is done by the task analysis and interviews. The data were analyzed by qualitative content analysis technique with a deductive approach that consists of four stages: preparation, organization, presentation and assessment data. The results showed that subjects capable of "reasoning high (ST)", "reasoning was (SS)" and "reasoning low (SR)" have a formal understanding in understanding the problem, which is marked by reading the questions, write down the known symbols appropriate and explain the meaning of the symbols used, asked to write their own sentences, followed by describing the image in accordance with the known along with logical explanations relating to images that have been created. Relational understanding a subject capable of "reasoning high" (ST) in the plan is a clear expression of the stage to be carried out in the plan from finding the value of x with extensive help to find the total cost required to make the fence in accordance with existing rules is accompanied by an explanation how and why the rules that apply. Understanding of instrumental subjects capable of "reasoning being (SS)" and the subject capable of "reasoning low (SR)" in the plan is a plan based on an existing rule that is by finding the value of x using the formula for the area trapezoid to determine the size of the trapezoid in fact, determine the size hypotenuse trapezoid with the Pythagorean formula followed by using roving in determining the overall manufacturing cost of the fence, knowing how the rules apply but did not explain the reason for using these rules. Understanding of instrumental subjects capable of "reasoning high (ST)", a subject capable of "reasoning being (SS)" and the subject capable of "reasoning low (SR)" in carrying out the plan that explains every step is done, explain verbally origin formula for the area trapezoid without being able proved mathematically and does not give the exact reason how the rule "moved segments" on the summation of which is applied in the completion, use properly Pythagoras calculation formula in determining the length of the hypotenuse trapezoidal without explanation of the origin of the Pythagorean formula. Understanding of instrumental subjects capable of "reasoning high (ST)", a subject capable of "reasoning being (SS)" and the subject capable of "reasoning low (SR)") in check is to verify results calculations starting from the first step to the last step and feel confident answers obtained is correct without being able to explain and prove the reasons why the answer obtained is correct